2014
DOI: 10.1007/s00439-014-1500-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium

Abstract: To identify genetic variants associated with refractive astigmatism in the general population, meta-analyses of genome-wide association studies were performed for: White Europeans aged at least 25 years (20 cohorts, N = 31,968); Asian subjects aged at least 25 years (7 cohorts, N = 9,295); White Europeans aged <25 years (4 cohorts, N = 5,640); and all independent individuals from the above three samples combined with a sample of Chinese subjects aged <25 years (N = 45,931). Participants were classified as case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 92 publications
(115 reference statements)
0
22
0
Order By: Relevance
“…Astigmatism has often been analysed as a dichotomous trait in genetic studies; however, the choice of the threshold used to define case/control status has varied from study to study (Fan et al 2011; Vitale et al 2008; Li et al 2015; Hammond et al 2001; Dirani et al 2010; Quek et al 2004; He et al 2004; Huynh et al 2007; Shah et al 2018). In an attempt to determine an optimal trait definition for detecting commonly occurring genetic markers with additive effects on astigmatism, we calculated SNP-heritability estimates with GCTA for corneal astigmatism and refractive astigmatism (and, for comparison, spherical equivalent) classified either as continuous or dichotomous traits, and using a grid of case thresholds for the latter (namely, 0.50, 0.75, 1.00, 1.25 and 1.50 D of astigmatism; or − 0.50, − 0.75, − 1.00, − 1.25 and − 1.50 D of spherical equivalent).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Astigmatism has often been analysed as a dichotomous trait in genetic studies; however, the choice of the threshold used to define case/control status has varied from study to study (Fan et al 2011; Vitale et al 2008; Li et al 2015; Hammond et al 2001; Dirani et al 2010; Quek et al 2004; He et al 2004; Huynh et al 2007; Shah et al 2018). In an attempt to determine an optimal trait definition for detecting commonly occurring genetic markers with additive effects on astigmatism, we calculated SNP-heritability estimates with GCTA for corneal astigmatism and refractive astigmatism (and, for comparison, spherical equivalent) classified either as continuous or dichotomous traits, and using a grid of case thresholds for the latter (namely, 0.50, 0.75, 1.00, 1.25 and 1.50 D of astigmatism; or − 0.50, − 0.75, − 1.00, − 1.25 and − 1.50 D of spherical equivalent).…”
Section: Resultsmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) for refractive astigmatism and corneal astigmatism have identified a single locus for each; in the promoter of PDGFRA (4q12) for corneal astigmatism (Fan et al 2011; Guggenheim et al 2013; Shah et al 2018) and near NRXN1 (2p16.3) for refractive astigmatism (Li et al 2015). Additional loci demonstrating suggestive association ( P  < 1 × 10 −5 ) for refractive astigmatism have been identified near the genes VAX2, TOX and LINC00340 (Li et al 2015; Lopes et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of different genes have been reported to be associated with myopia (Kiefer et al, 2013;Li et al, 2015a). Sibling risk ratio is high in myopia with the risk increasing with the severity of myopia (Guggenheim et al, 2000).…”
Section: Geneticsmentioning
confidence: 99%